Language and Group-based Power: Myths, Proverbs and Metaphors as Depositories of Gendered and Ethnic Identities in Perpetua Nkamanyang Lola’s Revised Edition of "The Lock on my Lips (2023)" - Nforbin, Gerald Niba (Advances in Social Sciences Research Journal, 2024)
Gender and Ethnicity are two types of group distinctions with which group-based power is associated and, in most postcolonial African urban contexts, gender and ethnicity intersect to shape our identities, opportunities and the challenges we face. Drawing from postcolonial, queer and feminist theories, this study examines the role of language in the construction of group-based power structures. The study examines the gender and ethnic specific function of Language (specifically myths, proverbs, metaphors, idioms and witty sayings) in the revised edition of Lola’s The Lock On My Lips with the view of demonstrating that the budding dramatist employs these linguistic devices to invest her work with a truly African sensibility and flavour, but mainly to show the role language plays in the social construction of gender and ethnic otherness.